Work instability versus mental health - Gavilán de Labourdette, Mirta Graciela (2002)
This contribution is part of a research on guidance and employment in La Plata, province of Buenos Aires (Argentina) undertaken jointly by the Chairs of Preventive Psychology and Vocational Guidance, both pertaining to the course of studies for Psychology at the National University of La Plata. This research is based on four axes, namely, education-work-social policies-health. This paper shall focus around the health axis, which is not provided with placement and employment services. Some unsystematical guidance experiences from the services of Adolescence and Mental Health are currently under way in the area. Research points to the existence of new demands of psychological treatment from a population (“the new poor”) afraid of losing their jobs -or even unemployed- who was not in the habit of going to the public hospital. In the casuistry explored here, people afraid of losing their jobs present more psychosomatic complexities. Local population is also analysed and the said analysis is linked with several national and international research projects.